Religion and Innovation - Bénabou, Roland; Ticchi, Davide; Vindigni, Andrea (American Economic Review, 2015)
In earlier work we identified a robust negative association between religiosity and patents per capita, holding across countries as well as US states. In this paper we relate 11 indicators of individual openness to innovation (e.g., attitudes toward science and technology, new versus old ideas, change, risk taking, agency, imagination, and independence in children) to 5 measures of religiosity, including beliefs and attendance. We use five waves of the World Values Survey and control for sociodemographics, country and year fixed effects. Across the 52 regressions, greater religiosity is almost uniformly associated to less favorable views of innovation, with high significance.